Lactobacillus plantarum ST-III culture supernatant ameliorates alcohol-induced cognitive dysfunction by reducing endoplasmic reticulum stress and oxidative stress - Xu, Zeping; Zhang, Jinjing; Wu, Junnan; Yang, Shizhuo; Li, Yuying; Wu, Yuyu; Li, Siyuan; Zhang, Xie; Zuo, Wei; Lian, Xiang; Lin, Jianjun; Jiang, Yongsheng; et al. (Frontiers in Neuroscience, 2022)
Background: Long-term alcohol exposure is associated with oxidative stress, endoplasmic reticulum (ER) stress, and neuroinflammation, which may impair cognitive function. Probiotics supplements can significantly improve cognitive function in neurodegenerative diseases such as Alzheimer’s disease. Nevertheless, the effect of Lactobacillus plantarum ST-III culture supernatant (LP-cs) on alcohol-induced cognitive dysfunction remains unclear. Methods: A mouse model of cognitive dysfunction was established by intraperitoneal injection of alcohol (2 g/kg body weight) for 28 days. Mice were pre-treated with LP-cs, and cognitive function was evaluated using the Morris water maze test. Hippocampal tissues were collected for biochemical and molecular analysis. Results: LP-cs significantly ameliorated alcohol-induced decline in learning and memory function and hippocampal morphology changes, neuronal apoptosis, and synaptic dysfunction. A mechanistic study showed that alcohol activated protein kinase R-like endoplasmic reticulum kinase (PERK) signaling and suppressed brain derived neurotrophic factor (BDNF) levels via ER stress in the hippocampus, which LP-cs reversed. Alcohol activated oxidative stress and inflammation responses in the hippocampus, which LP-cs reversed. Conclusion: LP-cs significantly ameliorated alcohol-induced cognitive dysfunction and cellular stress. LP-cs might serve as an effective treatment for alcohol-induced cognitive dysfunction.